2011
DOI: 10.1002/chem.201003100
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Properties of Free‐Base [14]Triphyrin(2.1.1) Compounds and the Formation of Subporphyrinoid Metal Complexes

Abstract: The synthesis of [14]triphyrin(2.1.1) compounds is described. In contrast with conventional subporphyrins, which consistently contain a central boron atom, free-base heteroaromatic compounds can be formed. A modified Lindsey method was used to prepare a range of different [14]triphyrins(2.1.1) in yields of up to 35% based on the reaction of diethylpyrrole (1a) and fused pyrroles of bicyclo[2.2.2]octadiene (BCOD) (2a-e) and dihydroethanonaphthalene (4a) with various aryl aldehydes. The concentration of BF(3)·OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
97
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 76 publications
8
97
1
2
Order By: Relevance
“…The peripheral moieties fused to the β‐carbon atoms of the pyrroles affected the electronic and optical properties of triphyrins more strongly than did changes in the meso aryl substituents. Triphyrin 14 with three peripheral dihydroethanonaphthalene pyrroles showed a B‐like band at 373 nm, which was similar to that of 11 and 13 (λ max= 379 nm in CH 2 Cl 2 ), and broad and weak Q‐like bands 22. [14]tri‐naphtho‐triphyrin(2.1.1) 15 was obtained quantitatively based on a retro Diels‐Alder reaction and exhibited a sharp and red‐shifted B band (447 nm) and a relatively intense Q band (Scheme ; Figure 3).…”
Section: Triphyrinsmentioning
confidence: 66%
See 2 more Smart Citations
“…The peripheral moieties fused to the β‐carbon atoms of the pyrroles affected the electronic and optical properties of triphyrins more strongly than did changes in the meso aryl substituents. Triphyrin 14 with three peripheral dihydroethanonaphthalene pyrroles showed a B‐like band at 373 nm, which was similar to that of 11 and 13 (λ max= 379 nm in CH 2 Cl 2 ), and broad and weak Q‐like bands 22. [14]tri‐naphtho‐triphyrin(2.1.1) 15 was obtained quantitatively based on a retro Diels‐Alder reaction and exhibited a sharp and red‐shifted B band (447 nm) and a relatively intense Q band (Scheme ; Figure 3).…”
Section: Triphyrinsmentioning
confidence: 66%
“…A further comprehensive study on the synthesis of [14]triphyrin(2.1.1) compounds revealed that the concentration of the BF 3 ⋅Et 2 O catalyst played a crucial role in determining the yield of the [14]triphyrin(2.1.1) macrocycle relative to the conventional tetrapyrrole porphyrin 22. During the Lindsey condensation of BCOD‐fused pyrrole and benzaldehyde, when 0.4 equivalent of BF 3 ⋅Et 2 O was used, the major product was found to be the tetraarylporphyrin.…”
Section: Triphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Commonly, triphyrins are known as subphthalocyanines and subporphyrins. Thus, [14]triphyrins(2.1.1) are available as monoanionic ligands and can be converted into diverse metal complexes, [8][9][10][11][12][13][14][15][16][17] as distinct from subphthalo cyanines and subporphyrins. We and others have developed the chemistry of [14]triphyrin(2.1.1), which has a relatively planar structure with 14π-electron aromaticity and can be isolated as a free base.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular interactions responsible for the stability of supramolecular structures are weak forces and consequently they require calculations with a high level of chemical accuracy [29][30][31][32][33]. Considering that single reference Hartree-Fock wave function theory (WFT) quantum mechanics and local density approximation (LDA) and even the generalized gradient approximation (GGA) KS-DFT do not have the accuracy required for the calculation of weak van der Waals-dispersion interactions/forces, both WFT and KS-DFT needed to be extended and even reformulated to be applied for the dispersion forces and interactions that are responsible for the stability of the noble gas dimers and stacked aromatics compounds.…”
Section: Introductionmentioning
confidence: 99%